"Hey, it is Rough Out Here": A Resilience Lens on the Biopsychosocial Circumstances of Homeless Older Persons in the City of Tshwane. Issue 3 (1st October 2020) - Geyer, Stephan
ABSTRACT: The biopsychosocial circumstances of homeless older persons (male and female, 55 years and older), specifically considered from a resilience lens, are inadequately described within the South African context. This study explored and described the biopsychosocial circumstances of homeless older persons in the City of Tshwane from a resilience lens. A qualitative research approach, operationalised through a collective case study, was implemented with 34 older persons across different research sites in the metropolitan area. Data were collected through semistructured interviews. Transcriptions of interviews were analysed through a process of thematic analysis. Apart from a brief profile, six themes are reported: (1) the choice of areas where homeless older persons reside, (2) the causes of homelessness, (3) the adversities they face, (4) coping strategies employed by homeless older persons, (5) the services and professionals homeless older persons utilised, and (6) the voices of participants concerning their recommendations for the City of Tshwane. Considered from a resilience lens, recommendations for an integrated social services delivery framework are offered for mitigating the harsh circumstances of homelessness among older persons.